HOLISTIC EDUCATION THROUGH CO-CURRICULAR ACTIVITIES - Shivani S; Rajesh PK (Asian Journal of Medicine & Health Sciences, 2019)
Holistic development is a process of selfrealization and learning which combines an individual’s mental, physical, social, emotional and spiritual growth.1 However, information management, digital skills and continuous learning are essential skills which a regular medical curriculum does not offer much focus on